Inkjet printing of NiO films and integration as hole transporting layers in polymer solar cells - Arjun Singh (Nature Portfolio, 2017)
Abstract Stability concerns of organic solar cell devices have led to the development of alternative hole transporting layers such as NiO which lead to superior device life times over conventional Poly(3,4-ethylenedioxythiophene) Polystyrene sulfonate (PEDOT:PSS) buffered solar cells. From the printability of such devices, it is imperative to be able to print NiO layers in the organic solar cell devices with normal architecture which has so far remained unreported. In this manuscript, we report on the successful ink-jet printing of very thin NiO thin films with controlled thickness and morphology and their integration in organic solar cell devices. The parameters that were found to strongly affect the formation of a thin yet continuous NiO film were substrate surface treatment, drop spacing, and substrate temperature during printing. The effect of these parameters was investigated through detailed morphological characterization using optical and atomic force microscopy and the results suggested that one can achieve a transmittance of ~89% for a ~18 nm thin NiO film with uniform structure and morphology, fabricated using a drop spacing of 50 μm and a heat treatment temperature of 400 °C. The devices fabricated with printed NiO hole transporting layers exhibit power conversion efficiencies comparable to the devices with spin coated NiO films.